Ultra-high strength concrete and its mixing method

By formulating ultra-high strength concrete with a low water binder ratio, high steel fiber content, and polyacetal fibers, along with a targeted coarse aggregate to steel fiber ratio, the challenges of gap passage and crack resistance are addressed, achieving superior performance in gap passing, crack resistance, and compressive strength.

JP7666936B2Active Publication Date: 2025-04-22SHIMIZU CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021010305
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-26
Publication Date
2025-04-22
Estimated Expiration
2041-01-26

AI Technical Summary

Technical Problem

Ultra-high strength concrete with high steel fiber mixing rates faces challenges in ensuring gap passage while maintaining crack resistance, as reducing coarse aggregate content to facilitate gap passage increases concrete shrinkage and decreases crack resistance.

Method used

The development of ultra-high strength concrete with a water binder ratio of 25% by mass or less and a steel fiber mixing rate greater than 0.5% by volume but less than 2% by volume, combined with the use of polyacetal fibers and a specific coarse aggregate to steel fiber mass ratio of 6.0 to 6.8, enhances both gap passing resistance and crack resistance.

Benefits of technology

This approach results in ultra-high strength concrete with excellent gap passing resistance, crack resistance, and compressive strength, while maintaining explosion resistance due to the inclusion of organic fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666936000005
    Figure 0007666936000005
  • Figure 0007666936000006
    Figure 0007666936000006
  • Figure 0007666936000001
    Figure 0007666936000001
Patent Text Reader

Abstract

To provide super high strength concrete of high steel fiber blend ratio, excellent in capability of passing through a gap and in crack resistance, and a preparation method therefor.SOLUTION: The super high strength concrete comprises cement, silica fume, water, coarse aggregate, fine aggregate, a chemical admixture, a steel fiber and an organic fiber, in which the water / binder ratio is 25 mass% or less and the blend ratio of the steel fiber is higher than 0.5 volume% and 2 volume% or lower, with the maximum size of the coarse aggregate being 25 mm or less, and the mass ratio of the coarse aggregate relative to the steel fiber represented by coarse-aggregate / steel-fiber being from 6.0 to 6.8.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ultra-high strength concrete and a method for mixing the same. [Background technology]

[0002] By lowering the water-binder ratio in concrete, the compressive strength of the concrete can be increased. However, when the water-binder ratio is low, the concrete is more likely to spall when exposed to high temperatures, such as during a fire. As a method for suppressing spalling, a method of blending organic fibers into concrete is known, and organic fibers are often blended into high-strength concrete (Patent Document 1). It has also been proposed to incorporate both organic fibers and steel fibers in concrete (Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4608176 [Patent Document 2] JP 2002-193654 A [Patent Document 3] Patent No. 4071983 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, the design strength has been set at 100N / mm 2 The above ultra-high strength concrete is now being used in components such as RC columns of ultra-high rise RC buildings. Mixing steel fibers into ultra-high-strength concrete is believed to be effective in suppressing the deterioration of strength due to cracks during earthquakes in ultra-high-rise RC buildings and the collapse of ends during extremely large earthquakes. In particular, if the mixing rate of steel fibers can be increased to more than 0.5% by volume, for example to about 1.0% by volume, it is believed that it will be possible to significantly improve the performance of the material as a component. However, when the steel fiber content is increased in ultra-high strength concrete, it is difficult to ensure the gap passing ability so that the steel fiber can be reliably filled into the gaps between the densely arranged column reinforcement bars and shear reinforcement bars. One way to ensure void permeability is to reduce the amount of coarse aggregate, but reducing the amount of coarse aggregate to the extent that void permeability can be ensured increases the amount of shrinkage of the concrete, which leads to a decrease in crack resistance. Patent Documents 1 to 3 do not consider mix design for achieving both gap passability and crack resistance of concrete.

[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an ultra-high strength concrete which has a high steel fiber content but is excellent in gap passability and crack resistance, and a method for mixing the same. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] Ultra-high strength concrete containing cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixtures, steel fiber, and organic fiber, the water-binder ratio being 25% by mass or less, and the mixing ratio of the steel fiber being more than 0.50% by volume and 2% by volume or less, The maximum dimension of the coarse aggregate is 25 mm or less, The ultra-high strength concrete has a mass ratio of the coarse aggregate to the steel fibers of 6.0 to 6.8. [2] The ultra-high strength concrete of [1], wherein the organic fibers contain polyacetal fibers. [3] The ultra-high strength concrete according to [1] or [2], wherein the organic fiber content is 0.1 to 0.4 volume %. [4] The ultra-high strength concrete of any of [1] to [3], wherein the steel fibers have a diameter of 0.15 to 0.9 mm and a length of 12 to 32 mm. [5] A method for mixing ultra-high strength concrete by mixing cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixture, steel fiber, and organic fiber, the water-binder ratio being 25% by mass or less, and the mixing rate of the steel fiber being more than 0.5% by volume and 2% by volume or less, The maximum dimension of the coarse aggregate is 25 mm or less, A method for mixing ultra-high strength concrete, wherein the mass ratio represented by the coarse aggregate / the steel fibers is 6.0 to 6.8. [6] The method for mixing ultra-high strength concrete according to [5], wherein the organic fiber contains polyacetal fiber. [7] The method for mixing ultra-high strength concrete according to [5] or [6], wherein the organic fiber content is 0.1 to 0.4 volume %. [8] The method for mixing ultra-high strength concrete according to any one of [5] to [7] above, wherein the steel fibers have a diameter of 0.15 to 0.9 mm and a length of 12 to 32 mm. Effect of the Invention

[0007] According to the present invention, it is possible to provide ultra-high strength concrete which has a high steel fiber content but is excellent in gap passability and crack resistance, and a method for mixing the same. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a diagram illustrating a box-shaped container used in a vibration box filling test in the examples. [Diagram 2] 1 is a graph showing the results of a vibration box filling test (filling height before and after vibration) in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following definitions of terms apply throughout the specification and claims. "Concrete" includes fresh concrete and hardened concrete. "Ultra-high strength concrete" has a design standard strength of 100N / mm 2 This shows concrete that is as above. "Water-binder ratio" refers to the ratio (mass %) of the mass of water to the total mass of the binder in fresh concrete. "Binder" is a material that hydrates in concrete, such as cement, silica fume, slag, fly ash, etc. "Steel fiber mixing ratio" refers to the ratio (volume %) of the volume of steel fiber to the total volume of the remainder after excluding steel fiber and organic fiber from concrete. The "mixture ratio of organic fibers" indicates the ratio (volume %) of the volume of organic fibers to the total volume of the remainder after excluding steel fibers and organic fibers from concrete. "Fine aggregate ratio" refers to the ratio (volume %) of the absolute volume of fine aggregate to the absolute volume of all aggregates in concrete. "Absolute volume" refers to the volume occupied by the aggregate particles, including the voids within the aggregate but not the voids between the aggregate particles.

[0010] (Ultra-high strength concrete) The ultra-high strength concrete of the present invention (hereinafter also referred to as "the concrete") contains cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixtures, steel fibers, and organic fibers.

[0011] As the cement, moderate-heat Portland cement and low-heat Portland cement are preferred because of their low heat of hydration, and low-heat Portland cement is more preferred.

[0012] The silica fume may be the silica fume known for use in concrete. The content of silica fume is preferably 9 to 20 mass % based on the mass of cement. If the content of silica fume is within the above range, the fluidity and gap passing property of the concrete are more excellent.

[0013] The water content is an amount that results in a water-binder ratio of 25% by mass or less, and is preferably 15 to 25% by mass, more preferably 15 to 20% by mass, and particularly preferably 16 to 18% by mass. If the water-to-binder ratio is 25% by mass or less, the strength is 100 N / mm 2 It is easy to obtain a compressive strength exceeding 100%. In addition, the flexural toughness coefficient tends to be high. When the flexural toughness coefficient is high, the width and number of cracks when they occur tend to be smaller, and crack resistance tends to improve. If the water-binder ratio is 15% by mass or more, the autogenous shrinkage strain tends to be small. If the autogenous shrinkage strain is small, the crack resistance tends to be improved. In addition, if the water-binder ratio is 15% by mass or more, the mixing rate of steel fibers has a large effect on the gap passability, and the present invention is highly useful.

[0014] Examples of coarse aggregate include crushed hard sandstone, crushed andesite, and crushed rhyolite. The surface dry density of the coarse aggregate is, for example, 2.55 to 2.7 g / cm 3 It may be. The coarse aggregate may have a coarse particle ratio of, for example, 6 to 6.6.

[0015] The maximum dimension of the coarse aggregate is 25 mm or less, and preferably 20 mm or less. The maximum dimension of the coarse aggregate is the dimension indicated by the nominal dimension of the smallest sieve among sieves through which 90% or more by mass of the coarse aggregate passes. If the maximum dimension of the coarse aggregate is 25 mm or less, it is easy to ensure gap passability. Examples of coarse aggregates having a maximum dimension of 25 mm or less include coarse aggregates having a maximum dimension of 25 mm, coarse aggregates having a maximum dimension of 20 mm, coarse aggregates having a maximum dimension of 15 mm, and coarse aggregates having a maximum dimension of 13 mm.

[0016] The content of the coarse aggregate is set taking into consideration the mass ratio of the coarse aggregate to the steel fiber and the unit bulk volume of the coarse aggregate in the concrete. The mass ratio of the coarse aggregate to the steel fiber will be explained in detail later.

[0017] Examples of fine aggregate include crushed sand, mountain sand, and land sand. The surface dry density of the fine aggregate is, for example, 2.55 to 2.7 g / cm 3 It may be. The content of fine aggregate is set taking into consideration the fine aggregate ratio.

[0018] As the chemical admixture, known ones can be used, and examples thereof include high-performance water reducing agents, high-performance AE water reducing agents, etc. These chemical admixtures may be used alone or in combination of two or more kinds.

[0019] The concrete preferably contains at least a high-performance water-reducing agent as a chemical admixture. Examples of high-performance water-reducing agents include those whose main component is a polycarboxylate ether, those whose main component is a polycarbohydrate copolymer, and the like. The content of the high-range water reducing agent is, for example, about 1 to 5 mass % relative to the mass of cement when the solid content of the main component is about 30%.

[0020] Examples of the steel material constituting the steel fibers include ordinary steel and stainless steel, and those having alkali resistance are preferable. From the viewpoint of rust prevention, it is preferable that the steel material surface is zinc plated. The shape of the steel fibers may be hook-shaped, straight, wavy, etc. From the viewpoints of improving the adhesion between the concrete and the steel fibers and improving the toughness of the concrete, the hook-shaped fibers are preferred. As the steel fibers, for example, those commercially available as steel fibers for steel fiber reinforced concrete can be used.

[0021] The length of the steel fibers is preferably 12 to 32 mm, more preferably 24 to 32 mm. If the length of the steel fibers is within the above range, the fibers will have better gap passing properties and crack resistance in concrete. The length of the steel fibers is measured with a vernier caliper or the like. The diameter of the steel fibers is preferably 0.15 to 0.9 mm, more preferably 0.38 to 0.75 mm. If the diameter of the steel fibers is within the above range, the fibers will have better gap passing properties and crack resistance in concrete. The diameter of the steel fibers is measured using a vernier caliper or the like.

[0022] In the present concrete, the mixing ratio of steel fiber is more than 0.5 volume % and not more than 2 volume %, and preferably 0.7 to 1.2 volume %. If the mixing ratio of steel fiber is more than 0.5 volume %, the present concrete has excellent toughness and crack resistance. If the mixing ratio of steel fiber is not more than 2 volume %, it is easy to ensure sufficient gap passability.

[0023] The mass ratio of coarse aggregate to steel fiber (hereinafter also referred to as "G / SF") is 6.0 to 6.8, preferably 6.0 to 6.3. When G / SF is equal to or more than the lower limit, crack resistance is excellent, and when it is equal to or less than the upper limit, gap passability is excellent.

[0024] Examples of the organic fibers include polyolefin fibers such as polypropylene and polyethylene, polyvinyl alcohol fibers (vinylon fibers), polyacetal fibers, etc. These organic fibers may be used alone or in combination of two or more. Among these, polyacetal fibers are preferred because they can exhibit sufficient anti-explosion effect even with a small mixing ratio. Polyacetal fibers may be used in combination with other organic fibers.

[0025] The polyacetal fiber is a fiber containing a polyacetal resin. Polyacetal resin is a homopolymer or copolymer that has an oxymethylene unit represented by [-CH2-O-]. The decomposition start temperature and end temperature of polyacetal resin are relatively low, and decomposition is completed in a short time. Therefore, polyacetal-based fibers have sufficient anti-explosion effect even with a small mixing rate compared to other organic fibers.

[0026] The polyacetal fiber may be made of only polyacetal resin, or may be a fiber containing polyacetal resin and other resins. Examples of other resins include polyolefin resins such as polyethylene and polypropylene, and polyvinyl alcohol resins. The proportion of the polyacetal resin in the polyacetal fibers is preferably 45% by mass or more based on the total mass of the polyacetal fibers.

[0027] The melt mass flow rate (MFR) of the polyacetal fiber is preferably 5 g / 10 min or more, and more preferably 20 g / 10 min or more, from the viewpoint of preventing explosive cracking. The MFR of polyacetal fibers is a value measured according to JIS K 6758 under conditions of 190°C and a load of 21.2N.

[0028] The dry density of polyacetal fibre is 1.41g / cm 3 When the dry density is within the above range, the dispersion of the fibers in the concrete is excellent. The dry density is measured according to JIS L 1015.

[0029] The length of the polyacetal fiber is preferably 9 to 11 mm, more preferably 9.5 to 10.5 mm. If the length of the polyacetal fiber is within the above range, the fiber has better gap passing property and better dispersibility in concrete. The length of the polyacetal fiber is measured according to JIS L 1015. The moisture content of the polyacetal fiber is preferably 20 to 40%, more preferably 30 to 40%. When the moisture content of the polyacetal fiber is within the above range, the dispersibility of the fiber in concrete is excellent. The moisture content of the polyacetal fiber is measured according to JIS L 1015.

[0030] The cross-sectional shape of the polyacetal fiber may be any of circular, irregular, hollow, etc. When the polyacetal fiber contains other resins, the polyacetal fiber may be a fiber made of a mixed resin of polyacetal resin and other resins, or may be a composite fiber having a layer made of polyacetal resin and a layer made of other resins. Examples of the form of the composite fiber include a parallel type, a core-sheath type, and a split type. Polyacetal fibers can be produced, for example, by the method described in Japanese Patent No. 4608176.

[0031] The ratio of the volume of the polyacetal fibers to the total volume of the organic fibers is preferably 80 volume % or more, more preferably 90 volume % or more, and may be 100 volume %.

[0033] In the present concrete, the organic fiber content is preferably 0.1 to 0.4 volume %, more preferably 0.2 to 0.3 volume %. When the organic fiber content is equal to or higher than the lower limit of the above range, the explosive resistance is superior, and when the organic fiber content is equal to or lower than the upper limit, sufficient gap passability is easily ensured.

[0034] This concrete can be mixed by mixing cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixtures, steel fiber, organic fiber, and other components as necessary so as to meet the specified water-binder ratio, steel fiber mixing rate, unit coarse aggregate bulk volume, etc.

[0035] In the concrete described above, the maximum dimension of the coarse aggregate is 25 mm or less, and the G / SF is 6.0 to 6.8. Therefore, although the water-binder ratio is low at 25 mass% or less and the steel fiber content is high at more than 0.5 vol% and 2 vol% or less, the concrete has excellent gap passability and crack resistance. In addition, this concrete has a low water-binder ratio of 25% by mass or less, and a high steel fiber content of more than 0.5% by volume and less than 2% by volume, so it has excellent strength (for example, a compressive strength of 110 to 180 N / mm2 at 28 days (4 weeks) measured according to JIS A 1108). 2 ) is obtained. In addition, since it contains organic fibers, it has explosion resistance.

[0036] (How to mix ultra-high strength concrete) The method for mixing ultra-high strength concrete of the present invention is a method for mixing cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixtures, steel fiber, and organic fiber to mix ultra-high strength concrete having a water-binder ratio of 25 mass% or less and a content of the steel fiber of more than 0.5 vol% and not more than 2 vol%. Other components may be mixed in addition to the cement, silica fume, coarse aggregate, fine aggregate, chemical admixture, steel fiber, and organic fiber. The cement, silica fume, coarse aggregate, fine aggregate, chemical admixture, steel fiber, organic fiber, and other components are the same as those described above.

[0037] In the preparation method of the present invention, G / SF is 6.0 to 6.8, preferably 6.0 to 6.3. When G / SF is equal to or more than the lower limit, crack resistance is excellent, and when it is equal to or less than the upper limit, gap passability is excellent.

[0038] The preferred ranges of the water-binder ratio and the mixing ratio of steel fibers are the same as those described above. The preferred amounts of silica fume, fine aggregate, chemical admixtures, organic fibers, etc., and the preferred ranges of the fine aggregate ratio are the same as those of the present concrete.

[0039] In the mixing method of the present invention, the target value V' of the unit coarse aggregate volume of the ultra-high strength concrete is calculated by the following formula (1): bG and calculating the target value V' bG It is preferable to set the mixing amount of the coarse aggregate so that

[0040] V' bG =V bG -(K S 2r G / 3r F -1)·V F / G S (1) Here, V' bG is the target value of the unit coarse aggregate bulk volume of the ultra-high strength concrete (m 3 / m 3 ), V bG is the unit coarse aggregate bulk volume of ultra-high strength concrete (m 3 / m 3 ) standard value range is 0.5 to 0.56 (m 3 / m 3 ) and K S is an influence coefficient, which is a number between 0.8 and 1 when the maximum dimension of the coarse aggregate is 15 mm or less, and is a number between 1 and 1.35 when the maximum dimension of the coarse aggregate is between 15 mm and 25 mm or less. rG represents the radius (mm) of the coarse aggregate calculated from the total surface area of ​​the coarse aggregate obtained from the particle size distribution of the coarse aggregate, assuming that the coarse aggregate is spherical, r F indicates the radius (mm) of the steel fiber calculated assuming the steel fiber to be cylindrical, V F indicates the mixing ratio (volume%) of the steel fiber, G S indicates the actual volume ratio (volume %) of the coarse aggregate. The actual volume ratio of coarse aggregate is measured according to JIS A 1104.

[0041] The smaller the maximum dimension of the coarse aggregate, the smaller the unit bulk volume of coarse aggregate required to ensure pore passage (i.e., the influence coefficient K S The influence coefficient K S If the influence coefficient K is equal to or greater than the lower limit, the gap permeability of the resulting ultra-high strength concrete is superior. S When the value is equal to or less than the upper limit, the crack resistance of the obtained ultra-high strength concrete is superior. When the maximum dimension of the coarse aggregate is 15 mm or less, the influence coefficient K S The preferred value is 0.9. When the maximum dimension of the coarse aggregate is more than 15 mm and not more than 25 mm, the influence coefficient K S is 1.2 is preferred.

[0042] In the mixing method of the present invention explained above, the maximum dimension of the coarse aggregate is set to 25 mm or less, and the G / SF is set to 6.0 to 6.8, so that ultra-high strength concrete with excellent gap passability and crack resistance can be mixed, even though the water-binder ratio is low at 25 mass% or less and the steel fiber mixing rate is high at more than 0.5 vol% and 2 vol% or less. The resulting ultra-high strength concrete has a low water-binder ratio of 25% by mass or less and a high steel fiber content of more than 0.5% by volume and less than 2% by volume, giving it excellent compressive strength. In addition, the concrete contains organic fibers, giving it explosive resistance. EXAMPLES

[0043] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these.

[0044] (Materials used) The materials used in the examples are shown in Table 1.

[0045] [Table 1]

[0046] (Mixture 1~5) <Mixing ultra-high strength concrete> According to Table 2, the materials were mixed in the following manner to prepare ultra-high strength concrete. W / C is designed with a standard strength of 100N / mm 2 The above was assumed and set. W / C is the mass ratio of water (W) to silica fume cement (C), and corresponds to the water-to-binder ratio. The unit weight of steel fiber is 80 kg / m 3 corresponds to a steel fiber mixing rate of 1% by volume. The unit weight of organic fiber (polyacetal fiber) is 3.10 kg / m 3 and 3.90 kg / m 3 These correspond to organic fiber mixing ratios of 0.2% and 0.3% by volume, respectively. In Table 2, "s / a" indicates the fine aggregate ratio. A forced biaxial mixer was used for mixing. Silica fume cement (C) and fine aggregate (S) were added and mixed dry, after which water (W) and chemical admixture (SP) were added and mixed to make mortar. Next, coarse aggregate (G) was added and mixed to make concrete. Polyacetal fiber (PA) and steel fiber (SF) were added and mixed for 90 seconds to make ultra-high-strength concrete containing steel fiber.

[0047] [Table 2]

[0048] <Evaluation> The mixed ultra-high-strength concrete containing steel fibers was subjected to measurements of slump flow, flow time, air content, concrete temperature, unit volume mass, filling time and height into a box-shaped container, and filling time and height under vibration, as well as hardened concrete properties (compressive strength (at 28 days), flexural toughness coefficient (at 28 days), and autogenous shrinkage strain (at 91 days)). Slump flow and flow time were measured according to JIS A 1150, air content according to JIS A 1128, concrete temperature according to JIS A 1156, unit volume mass according to JIS A 1116, compressive strength according to JIS A 1108, and flexural toughness coefficient according to JSCE-G552-2013.

[0049] The filling time and height, and the vibration filling time and height were measured using the vibration box filling test method in accordance with the Japan Society of Civil Engineers standards (JSCE-F511-2012, JSCE-F701-2016). In the vibration box filling test, a box-shaped container 1 as shown in Figure 1 is used. The bottom surface 2 of the box-shaped container 1 is made of a vibration-proof rubber mat, and the side wall 3 is made of a transparent acrylic plate. The inside of the box-shaped container 1 is divided into rooms A and B by a partition 4. A rod-shaped vibrator 5 is placed in room A. The vibrator 5 is a hand-held vibrator that is driven by an external motor and conforms to JIS A 8610, and the vibrator has a nominal diameter of 28 mm, a length of 580 mm or more, and a vibration frequency of about 200 Hz. A gate G is placed at the bottom end of the partition 4, and a flow obstacle 6 is placed in the gate G. The gate G can be opened and closed by raising and lowering the partition plate 7 placed along the partition 4. The unit of the values ​​indicating the dimensions in the figure is mm. Since the minimum gap dimension between the mechanical joints embedded in the precast members may be less than 40 mm, the flow obstacle 6 is obstacle R2 (D13 rebar x 3, 35 mm interval). In the vibration box filling test, with gate G closed, concrete is poured into chamber A up to the top, and the tip of vibrator 5 is placed at a position 100 mm above the bottom of chamber A. Next, gate G is opened, and concrete is allowed to flow from chamber A to chamber B without vibrating vibrator 5, and the height from the bottom to the top of the concrete that has flowed into chamber B (filling height before vibration) is measured. Next, vibrator 5 is vibrated, and the height from the bottom to the top of the concrete that has flowed into chamber B (filling height after vibration) is measured.

[0050] The autogenous shrinkage strain was measured in accordance with the Autogenous Shrinkage Test Method for High-Fluidity Concrete (tentative title) in the Japan Concrete Institute: Super-Fluidity Concrete Research Committee Report (II), pp.209-210, May 1994, [Appendix 1]. A Tokyo Measuring Instruments Laboratory embedded strain meter KM-100BT was installed in the centre of a 10 x 10 x 40 cm test specimen.

[0051] The measurement results of slump flow, flow time, air content, concrete temperature, unit volume mass, filling time / height, vibration filling time / height, compressive strength, flexural toughness coefficient, autogenous shrinkage strain, and flexural toughness coefficient / compressive strength ratio are shown in Tables 3 and 4. In addition, the filling height (filling height before vibration) and vibration filling height (filling height after vibration) are shown in Figure 2. The slump flow, air content and compressive strength of mixes 1 to 5 satisfied the required quality.

[0052] Comparing mixes 1 to 3, which have a water-binder ratio of 17.0%, mixes 1 and 2, which have a G / SF of 9.1 or 11.1, did not reach a vibration-filled height of 300 mm and had poor gap passability. In contrast, mix 3, which has a G / SF of 6.1, did not experience blockage in the vibration box filling test and reached a vibration-filled height of 300 mm, showing excellent gap passability. Mix 3 also has a smaller autogenous shrinkage strain and a larger flexural toughness coefficient than mixes 1 and 2, indicating that it also has excellent crack resistance. Mixtures 4 to 5, which had different water-binder ratios, also showed excellent gap permeability, with no blockages occurring in the vibration box filling test and the vibration filling height reaching 300 mm. Comparing mixes 3 to 5, it was confirmed that the smaller the water-binder ratio, the higher the filling height before shaking (the higher the gap permeability). It is presumed that the viscosity of the base concrete affected the gap permeability. From the ratio of flexural toughness coefficient / compressive strength of mixes 1 to 5, it can be seen that mixes 3 to 5 have a larger flexural toughness coefficient per unit compressive strength than mixes 1 and 2, and are superior in crack resistance.

[0053] [Table 3]

[0054] [Table 4]

[0055] The steel fiber mixing rate V F is 1 (volume %), and the unit coarse aggregate bulk volume V' of ultra-high strength concrete containing steel fibers bG is 0.300(m 3 / m 3 In the formulations 3 to 5, each value in the formula (1) is V bG is 0.5, r G is 5.35, r F is 0.31, V F is 0.01002, G S is 0.6, and K S became 1.2.

Claims

1. An ultra-high strength concrete comprising cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixture, steel fiber, and organic fiber, the water-binder ratio being 25% by mass or less, and the mixing ratio of the steel fiber being more than 0.50% by volume and 2% by volume or less, The maximum dimension of the coarse aggregate is 25 mm or less, The mass ratio represented by the coarse aggregate / the steel fibers is 6.0 to 6.8; The organic fiber content is 0.1 to 0.4 volume %; Ultra-high strength concrete with a fine aggregate ratio of 64.3 to 67.2%.

2. The ultra-high strength concrete according to claim 1 , wherein the organic fibers include polyacetal fibers.

3. 3. The ultra-high strength concrete according to claim 1 or 2, wherein the steel fibers have a diameter of 0.15 to 0.9 mm and a length of 12 to 32 mm.

4. A method for mixing ultra-high strength concrete comprising mixing cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixture, steel fiber, and organic fiber, the method comprising the steps of: mixing the cement, silica fume, water, coarse aggregate, fine aggregate, chemical admixture, steel fiber, and organic fiber; mixing the water-binder ratio of the concrete to the ultra-high strength concrete; and mixing the steel fiber to the ultra-high strength concrete; the water-binder ratio of the ultra-high strength concrete being 25% by mass or less and the mixing ratio of the steel fiber being more than 0.5% by volume and not more than 2% by volume, the method comprising the steps of: The maximum dimension of the coarse aggregate is 25 mm or less, The mass ratio represented by the coarse aggregate / the steel fibers is 6.0 to 6.8; The organic fiber content is 0.1 to 0.4 volume %; A method for mixing ultra-high strength concrete with a fine aggregate ratio of 64.3 to 67.2%.

5. 5. The method for mixing ultra-high strength concrete according to claim 4, wherein the organic fibers include polyacetal fibers.

6. 6. The method for mixing ultra-high strength concrete according to claim 4 or 5, wherein the steel fibers have a diameter of 0.15 to 0.9 mm and a length of 12 to 32 mm.

Citation Information

Patent Citations

  • Cement mixed body having high toughness and refractoriness

    JP2002193654A

  • Synthetic fiber for explosive fracture resistant cement structure and explosive fracture resistant cement structure

    JP2003160366A

  • Explosion-resistant concrete

    JP2003306366A

  • Composite concrete for floor slabs and rafts

    JP2013508261A

  • Mixing method of ultra high strength concrete

    JP2019214493A